Brain's Alpha, Beta, Gamma, delta, and theta oscillations in neuropsychiatric diseases: Proposal for biomarker strategies - Başar Eroğlu, Canan; Güntekin, Bahar; Gülmen Yener, Görsev; BAŞAR, EROL (My University, 2013)
Brain oscillations have gained tremendous importance in neuroscience during recent decades as functional building blocks of sensory-cognitive processes. Research also shows that event-related oscillations (EROs) in "alpha," "beta," "gamma," "delta," and "theta" frequency windows are highly modified in pathological brains, especially in patients with cognitive impairment. The strategies and methods applied in the present report reflect the innate organization of the brain: "the whole brain work." The present paper is an account of methods such as evoked/event-related spectra, evoked/ERDs, coherence analysis, and phase-locking. The report does not aim to cover all strategies related to the systems theory applied in brain research literature. However, the essential methods and concepts are applied in several examples from Alzheimer's disease (AD), schizophrenia, and bipolar disorder (BD), and such examples lead to fundamental statements in the search for neurophysiological biomarkers in cognitive impairment. An overview of the results clearly demonstrates that it is obligatory to apply the method of oscillations in multiple electroencephalogram frequency windows in search of functional biomarkers and to detect the effects of drug applications. Again, according to the summary of results in AD patients and BD patients, multiple oscillations and selectively distributed recordings must be analyzed and should include multiple locations. Selective connectivity between selectively distributed neural networks has to be computed by means of spatial coherence. Therefore, by designing a strategy for diagnostics, the differential diagnostics, and application of (preventive) drugs, neurophysiological information should be analyzed within a framework including multiple methods and multiple frequency bands. The application of drugs/neurotransmitters gains a new impact with the analysis of oscillations and coherences. A more clear and differentiated analysis of drug effects can be attained in comparison to the application of the conventional wide-band evoked potential and event-related potential applications.